Changes in the Disease Spectrum of Hospitalized Children in a County Hospital of China - Liu, Yonglin; Liu, Juan; Shamsi, Bilal Haider; Hao, Xiao Xia (Journal of Nepal Paediatric Society, 2016)
Introduction: Considering the present situation of disease spectrum changes, it is very important to understand the changes of disease in primary settings, to find out the feature of disease area, to direct the decision making so as to allocate the medical resources accordingly. The objectives of this study were to understand the changing trends in disease spectrum and mortality rate of children hospitalised in the department of paediatrics in Shenmu hospital, and to provide scientific basis for the future medical care and prevention of childhood diseases. Material and Methods: A retrospective statistical analysis was done using the data regarding hospitalization of children in Shenmu County. The study lasted fifteen years, from January 1998 to December, 2012. Results: A total of 23,448 children were hospitalized below the age of 14. Majority of the patients were younger than three years old constituting 78.8% (which included age 1 month 1 year 57.2%). The average number of days of hospitalization was 6 8 days, with a median time of six days. The leading cause of hospitalization was respiratory disease. Other major illnesses causing hospitalization included: infectious diseases, digestive tract diseases, neonatal diseases and nervous system diseases. A total of 144 children died during this period. The top three causes of death were: asphyxia, premature birth and neonatal respiratory distress syndrome. Conclusion: The changing trends in paediatric disease hospitalisations and mortality rate over the 15 years are significant for clinicians so as to prevent and minimise such diseases by appropriate preventive and therapeutic options to contain them. J Nepal Paediatr Soc 2016;36(1):19-23